Genetic Analysis of Birnirk Inuit from the Alaskan North Slope - Unkel, Sarah L.; Norman, Lauren E.Y.; Tackney, Justin; Krus, Anthony M.; Jensen, Anne M.; Alix, Claire; Mason, Owen; O'Rourke, Dennis H. (The Arctic Institute of North America, 2022)
Archaeological evidence indicates that Birnirk peoples (AD 650 – 1300) are the proposed genetic ancestors of the Thule Inuit (AD 950 – 1400) and are potentially an intermediary population between the Thule Inuit and earlier Old Bering Sea people (AD 1 – 1000). We sequenced the first hypervariable region of the mitochondrial DNA of 22 clearly associated Birnirk individuals from the Piġniq (Birnirk), Kugok, Kugusugaruk, and Nunavak sites on the North Slope of Alaska. Haplotypes A2a, A2a1, A2a3, A2b1, and D4b1a2a1a were identified in this population, demonstrating an expansion of Birnirk maternal genetic diversity. Maternal lineages from these individuals were evaluated with other past and contemporary Inuit populations from the Chukotka Peninsula to eastern Greenland. Our findings confirm Birnirk Inuit as probable maternal ancestors to Thule Inuit and may be among the first peoples possessing these lineages to have moved into the western North American Arctic from the Bering Strait region. Selon des preuves archéologiques, les Birnirks (650 à 1300 A.D.) sont les ancêtres génétiques proposés des Inuits thuléens (950 à 1400 A.D.) et pourraient représenter une population intermédiaire entre les Inuits thuléens et un peuple antérieur du Vieux Béring (1 à 1000 A.D.). Nous avons séquencé la première région hypervariable de l’ADN mitochondrial de 22 individus se rapportant manifestement aux Birnirks en provenance des sites Piġniq (Birnirk), Kugok, Kugusugaruk et Nunavak sur le versant nord de l’Alaska. Les haplotypes A2a, A2a1, A2a3, A2b1 et D4b1a2a1a ont été identifiés au sein de cette population, ce qui démontre une expansion de la diversité génétique maternelle des Birnirks. Les lignées maternelles de ces individus ont été évaluées par rapport à d’autres populations anciennes et contemporaines d’Inuits, allant de la péninsule des Tchouktches jusqu’à l’est du Groenland. Nos constatations permettent de confirmer que les Inuits birnikiens sont les ancêtres maternels probables des Inuits thuléens et qu’ils pourraient ...